2020
DOI: 10.3389/fpubh.2020.00400
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Prevalence of Dyslipidemia and Influencing Factors for Young Health Examination Cohort: A Cross-Sectional Survey

Abstract: The objective of this study was to estimate the prevalence of dyslipidemia and associated influencing factors in young adults in the southeastern coastal area of China. Methods: This study adopted a cross-sectional survey and included 7,859 young people who underwent examinations at three hospitals in Wenzhou, Zhejiang Province, China. All subjects completed a questionnaire in the form of face-to-face interviews and underwent anthropometric measurements and biochemical tests. The continuous data are presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
8
18
1
Order By: Relevance
“…In agreement with one study [ 30 ], our study also revealed that alcohol consumption was statistically associated with the prevalence of dyslipidemia. The relationship between alcohol intake and plasma lipid levels has been studied for decades and is controversial.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with one study [ 30 ], our study also revealed that alcohol consumption was statistically associated with the prevalence of dyslipidemia. The relationship between alcohol intake and plasma lipid levels has been studied for decades and is controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Compared to women, men had lower levels of HDL-C and signi cantly higher levels of total cholesterol, LDL-C, triglycerides. This nding was similar to that of the previous study, in which a high incidence of dyslipidemia was observed in males than in females [4][5][6].…”
Section: Discussionsupporting
confidence: 92%
“…According to World Bank estimates, the number of stroke and coronary heart disease will increase to 31.77 million and 22.63 million respectively by 2030[9]. Zhang et al [4] found that the prevalence of dyslipidemia in the young population in Wenzhou is relatively high. Young people should increase their health promoting behaviors and consider the factors in uencing dyslipidemia to lower the prevalence of dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…The association between drinking and plasma lipid levels has been studied for decades and remains controversial [ 28 ]. It has been shown that moderate alcohol consumption may increase levels of HDL-C, APO-A, and decrease levels of LDL-C [ 18 ]. This is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption plays an important role in the process of weight gain [ 10 , 11 , 12 , 13 , 14 , 15 ], as it provides a potential source of energy just after fat [ 16 ]. Alcohol consumption is a well-known determinant of serum lipids levels [ 17 , 18 , 19 ]. Moderate alcohol consumption appears to raise levels of high-density lipoprotein cholesterol (HDL-C) and triglyceride (TG) while lowering levels of low-density lipoprotein cholesterol (LDL-C), whereas heavy alcohol consumption has an unfavorable effect on serum lipids and lipoproteins [ 20 ].…”
Section: Introductionmentioning
confidence: 99%